Just let me preach: the biography of Paul Tassell - Osborne, Nathan O. (Regular Baptist Press, 2002)
A terrific trio -- Lightweight champion of the world -- Bob Jones University -- Second Baptist Church, Elberton, Georgia -- Doris Jaeger -- Bethany Baptist Church, Galesburg, Illinois -- The crown of rejoicing -- Campus Baptist Church, Ames, Iowa -- The glory years -- Contending for the faith -- National youth representative -- Grandview Park Baptist Church, Des Moines, Iowa -- National representative -- The GARBC -- Fifty years a preacher -- Just let me preach